(untitled) (Student Conference Proceedings, 2025)
Conducting experiments with infants poses unique challenges. During the investigation of brain responses on social perception of infants, specific difficulties, such as increased mobility, arose regarding 11-month-olds. To address these, we modified the experimental setup and conducted a pilot study with 11-month-old infants (N = 8), recording electroencephalographic (EEG) signals using two different EEG preprocessing pipelines (an open-science vs. a custom pipeline). We analyzed the Nc (Negative central) response to familiar vs. unfamiliar faces and to happy vs. fearful expressions. While no significant differences were found, possibly due to the small sample size, the setup changes proved effective, with standard retention rates for valid and clean trials. No significant differences in data between pipelines indicate the effectiveness of both, highlighting the reliability of open-science tools in infant EEG research. However, the custom pipeline’s small amplitudes in Nc responses emphasize the need for further validation in a larger sample.